Time delay estimation of signals using quadratic time prequency distribution [electronic resource] - Zubairu Abdulmumini Loko, 1985- author; Ahmad Zuri Sha'ameri; Fakulti Kejuruteraan Elektrik (2014)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2014